2015
DOI: 10.1530/eje-15-0185
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function, as assessed by TSH, and future risk of venous thromboembolism: the Tromsø study

Abstract: Objective: The relationship between thyroid function and the risk of venous thromboembolism (VTE) has not been addressed in population-based cohorts. We investigated the association between TSH levels and the risk of VTE in a general adult population. Design: Population-based cohort study. Methods: TSH was measured in 11 962 subjects aged 25-89 years who participated in Tromsø 4-6 starting in 1994-1995. Incident VTE events were recorded through 31st December 2010. Cox's regression models with TSH as a time-var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Data on SCTD and VTE are limited. A recently published prospective cohort study on 11 900 subjects aged 25–89 years found a non‐significantly increased risk for rVTE among patients with elevated and decreased TSH values as compared with healthy controls (respectively: HR 1.55, 95% CI 0.87–2.77; and HR 2.16, 95% CI 0.69–6.76). The results of this previous study were limited by the absence of fT4 measurements, so that the authors could not discriminate between overt and subclinical forms of thyroid dysfunction, and CIs were rather wide.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data on SCTD and VTE are limited. A recently published prospective cohort study on 11 900 subjects aged 25–89 years found a non‐significantly increased risk for rVTE among patients with elevated and decreased TSH values as compared with healthy controls (respectively: HR 1.55, 95% CI 0.87–2.77; and HR 2.16, 95% CI 0.69–6.76). The results of this previous study were limited by the absence of fT4 measurements, so that the authors could not discriminate between overt and subclinical forms of thyroid dysfunction, and CIs were rather wide.…”
Section: Discussionmentioning
confidence: 98%
“…Only one recent prospective cohort study found that TSH levels below or above the normal range were non‐significantly associated with a moderately increased risk for VTE. However, this study was limited by the absence of free thyroxine (fT4) measurements, and could therefore not differentiate between overt and subclinical forms of thyroid dysfunction . As no prospective data on SCTD and rVTE are currently available, we aimed to investigate a possible association between SCTD and rVTE as well as all‐cause mortality in a large cohort of elderly patients with VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Other case-cohort and case-control studies have also shown a link between hyperthyroidism and risk of VTE [41,42]. A recent study by Lerstad et al showed a two-fold increased risk of VTE in patients with low TSH when compared to healthy patients [39]. This is because hyperthyroidism or subclinical hyperthyroidism increases the release of von Willebrand factor (VWF), plasminogen activator inhibitor-1 (PAI-1), factor III, and factor IX [32,43].…”
Section: Thyroid Function and Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…The combination of pulmonary embolism (PE) and deep vein thrombosis (DVT), termed as venous thromboembolism (VTE), is associated with numerous complications. One study published in 2004 stated that around 370,000 deaths in six European countries were due to VTE [39,40]. A large registry-based study of around 20 million people showed a clear link between hyper-and hypothyroidism and events of VTE in their lifetime.…”
Section: Thyroid Function and Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…4 The exact pathophysiologic mechanisms explaining the relation between thyrotoxicosis and thrombosis are not fully understood and there is insufficient evidence to demonstrate a strong causal relation between these 2 phenomena. 4,5 However, it has been hypothesized that changes in the levels of thyroid hormones can lead to disequilibrium in the coagulation cascade. Hyperthyroidism can result in either increased synthesis or impaired clearance of multiple proteins that are mainly derived from the vascular endothelium, leading to elevated levels of molecules such as factor VIII, factor IX, von Willebrand factor, fibrinogen, fibronectin, and plasminogen activator inhibitor-1, therefore favoring a procoagulant state.…”
Section: Oy-stersmentioning
confidence: 99%